Quantifying the transportation related risks in the transportation of avocados from farm to packhouse using Bayesian Networks - Steyn, Wynand J.vdM. (University of Pretoria, 2021)
Dissertation (MEng (Transportation Engineering))--University of Pretoria, 2020.